2022
DOI: 10.1186/s13690-021-00713-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality among TB-HIV co-infected children attending anti-retroviral therapy clinics of selected public hospitals in southern, Ethiopia: retrospective cohort study

Abstract: Background Co-infection of tuberculosis and HIV has a significant impact on public health. TB is the most common opportunistic infection and the leading cause of death in HIV-positive children worldwide. But there is paucity of studies concerning the predictors of mortality among TB-HIV co-infected children. This study aimed to determine the predictors of mortality among TB-HIV co-infected children attending ART clinics of public hospitals in Southern Nation, Nationalities and Peoples Region (S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…A total of seven studies [21,24,25,33,38,43,47] provided data on mortality rates among children and adolescents with HIV-TB co-infection across various age groups. The pooled mortality rates were 32% (95% CI [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] for those aged <12 months, 14% (95% CI [10][11][12][13][14][15][16][17][18][19] for the 1-5 years age group, 15% (95% CI 12-17) for the 5-10 years age group, and 16% (95% CI [13][14][15][16][17][18][19][20] for those aged over 10 years old (Figure 4, Supplemental Digital Content, http://links.lww.com/QAD/D142).…”
Section: Subgroup Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of seven studies [21,24,25,33,38,43,47] provided data on mortality rates among children and adolescents with HIV-TB co-infection across various age groups. The pooled mortality rates were 32% (95% CI [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] for those aged <12 months, 14% (95% CI [10][11][12][13][14][15][16][17][18][19] for the 1-5 years age group, 15% (95% CI 12-17) for the 5-10 years age group, and 16% (95% CI [13][14][15][16][17][18][19][20] for those aged over 10 years old (Figure 4, Supplemental Digital Content, http://links.lww.com/QAD/D142).…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…3, a statistically significant lower risk of death was observed in the 1-5 years age group (OR 0.40; 95% CI 0.20-0.78; P < 0.05), the 5-10 years age group (OR 0.34; 95% CI 0.16-0.72; P < 0.05), and the over 10 years age group (OR 0.35; 95% CI 0.22-0.55; P < 0.05) when compared with those under 12 months. Data from nine studies [21,24,25,27,33,36,38,43,52] reported mortality rates among children and adolescents with HIV-TB co-infection, stratified by gender. The combined mortality rates were 12% (95% CI 9-16) for males and 10% (95% CI 7-16) for females (Figure 5, Supplemental Digital Content, http://links.lww.com/ QAD/D142).…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…By 2019, tuberculosis (TB) had surpassed HIV/AIDS as the leading cause of infectious agent-related deaths worldwide, with an estimated 10.1 million new cases and 1.7 million fatalities, marking a significant shift before 2020. 11,12 In sub-Saharan Africa, incidence rates for children and adolescents are high, with 2,017 cases per 100,000 patient-years (20). The twin epidemic of TB and HIV caused 0.3 million deaths worldwide in 2017, with a lifetime risk increase from 15% to 22% (1).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 According to the WHO 2019 report, TB caused 10.1 million new cases and 1.7 million deaths, making it the leading cause of death from a single infectious agent (9). In Africa, the resurgence of TB is linked to TB-HIV/AIDS connection and a shortage of skilled healthcare personnel, not control program deterioration 5,6 In Africa, TB is the second largest disease burden (25%), following Southeast Asia (44%) (12,13). Additionally, one-third of HIV-associated deaths are attributed to TB (9,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation